The Tradition of Melayokaken in Using Society: The Causal Factors and Its Impacts - Akhmad Haryono; Akhmad Sofyan; Samudji Samudji (Humaniora, 2017)
This article discusses the tradition of Melayokaken, the causal factors, and the impacts of the tradion on Using Society in Banyuwangi. Melayokaken, as a tradition of elopement, had been maintained by Using community for a long time. For some Using People in Banyuwangi (UPB), this tradition was regarded as a pride because it could help to maintain the tradition that had been formed since the time of their ancestors. But on the other hand, melayokaken tradition is considered violating the norms followed by Using people, namely religious norms, anti conflicts and living in peace. The method used in this study is qualitative method. Data were collected through participatory observations, interviews, notings, and recordings. The method of analysis used in this research is descriptive qualitative method. This research resulted in the finding that there is a factor that can maintain the tradition of melayokaken, namely as an alternative means to resolve the impasse communication in entering the marriage, for example due to: differences in status and social class, educational factors, the bride family may not marry more than one time in a year, the bridegroom candidate has not got a job yet, the candidates of the bride and the bridegroom are not yet old enough, the birth dates of the two are not good and matched, the marriage must not precede an older sister marriage, the bride candidate has already been betrothed by parents.This entails two impacts of the tradition, namely positive and negative. The positive side proves that melayokaken can penetrate the gap in status and social class between the two families and the things which are recognized less rational in the contemporary perspective. And the negative side proves that melayokaken had violated the norms, ethics, and religious values embraced by Using society although there was no significant impact on the doers’ social lives and in the community.